Public Versus Private Corporate Governance: The Role of The Board of Directors’ Structure in Conveying A Model of Corporate Governance - From An Employee’s Viewpoint - Auffret, Guilhem (2012)
This paper examines the discrepancies between corporate governance in the public and private sectors. Whilst current research has emphasized important theories of corporate governance, little attention has been paid to the disparity between both sectors. We focus our research on board composition, and specifically on the model it should convey to the employees of the firm. Six aspects of board composition were chosen to conduct this research: non-executive directors (or external members), board size, ethnicity representation, female directors, political connections and staff representation. By means of a qualitative analysis, we collected employees’ perceptions of each of these topics. We then undertook both content and narrative analyses to draw conclusions and compare them to the current literature’s findings. We find that some aspects of board composition may hold different degrees of importance and convey dissimilar models of governance to the employees depending on the sector they belong to. We also find that the current literature’s findings about boards of directors are more relevant to private than to public organizations.